2019
DOI: 10.1038/s41598-019-48944-1
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic effectiveness and ecologically adaptive traits of native rhizobial symbionts of Bambara groundnut (Vigna subterranea L. Verdc.) in Africa and their relationship with phylogeny

Abstract: Bambara groundnut ( Vigna subterranea L. Verdc.) is an indigenous, drought-tolerant, underutilized African food legume, with the ability to fix atmospheric N 2 in symbiosis with soil bacteria called rhizobia. The aim of this study was to assess the morpho-physiological, symbiotic and phylogenetic characteristics of rhizobia nodulating Bambara groundnut in Ghana, Mali and South Africa. The morpho-physiologically diverse isolates tested were also found to exhibit dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 47 publications
7
31
0
Order By: Relevance
“…IV (1.6%), and B. liaoningense (1.49%) (Figure 3A). The predominance of B. elkanii and B. pachyrhizi was in accordance with the previous reports for rhizobia of other Vigna species such as V. radiata, V. unguiculata, Vigna subterranea, and V. angularis (Zhang et al, 2007;Yang et al, 2008;Han et al, 2009;Ibny et al, 2019;Puozaa et al, 2019). The super dominance and ubiquitous distribution in the 11 sampling sites of B. elkanii, B. pachyrhizi, and B. ferriligni (Figure 3 and Table 1) demonstrated them as the most adapted or affinity symbionts of V. minima in the study area.…”
Section: Discussionsupporting
confidence: 92%
“…IV (1.6%), and B. liaoningense (1.49%) (Figure 3A). The predominance of B. elkanii and B. pachyrhizi was in accordance with the previous reports for rhizobia of other Vigna species such as V. radiata, V. unguiculata, Vigna subterranea, and V. angularis (Zhang et al, 2007;Yang et al, 2008;Han et al, 2009;Ibny et al, 2019;Puozaa et al, 2019). The super dominance and ubiquitous distribution in the 11 sampling sites of B. elkanii, B. pachyrhizi, and B. ferriligni (Figure 3 and Table 1) demonstrated them as the most adapted or affinity symbionts of V. minima in the study area.…”
Section: Discussionsupporting
confidence: 92%
“…These isolates presented a great genetic diversity and grouped respectively with various reference strains, in This variability in symbiotic efficiency is linked to the genetic diversity of these strains revealed by the phylogenetic tree of the 16S RNA gene. This information is consistent with results reported by Guei et al, (2019) and Ibny et al, (2019) who respectively identified and authenticated the rhizobia associated with Bambara groundnut in Côte d'Ivoire. Indeed, the inoculation of each plant was done with 1 mL of bacterial broth induced the average number and dry matter of nodule per plant varying respectively from 18 to 87 and 21,67 to 289,33 mg. however, Kumari et al, (2010) authenticated the rhizobia isolated from Indigofera species and reported that the average number of nodule varied depending on species.…”
Section: Phylogenetic Analysis Of the 16s-rrna Genesupporting
confidence: 92%
“…On solid YEM medium, these bacterial isolates forming gummy colonies with rapid growth were phenotypically diverse in terms of appearance, shape, size and color of the colonies which evoke the rhizobia. It confirms the results reported by Ibny et al, (2019) who revealed that the rhizobial isolates nodulating the Bambara groundnut in Africa showed a great morpho-physiological diversity, which varied from differences in size, shape and texture of the colonies. Gnangui et al, (2019) also reported that rhizobia isolated from the Bambara groundnut rhizosphere in Côte d'Ivoire had rapid growth.…”
Section: Isolation Of Bacteria From Bambara Groundnutsupporting
confidence: 91%
See 2 more Smart Citations